The legal pluralism in Malaysia - Shuaib, Farid Sufian (2018)
The paper examine the state of legal pluralism in Malaysia and its implication to the sources of law and the court systems. It also consider the consequences of legal pluralism in the relations between people of difference races and religions. The paper seeks to analyse possible solutions to the conflicts.